2003
DOI: 10.1016/s1071-55760300116-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leukocyte Traffic and Activation in Parturition

Abstract: Immune cell trafficking and activation are part of the initial mechanism that promotes ripening of the cervix, enhances uterine contractility, and initiates parturition. Markers for the conclusion of pregnancy may have diagnostic or therapeutic value to assess the normal progress of labor or identify women at risk of preterm labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 206 publications
6
21
0
1
Order By: Relevance
“…The cytokines, among other putative effects, recruit leukocytes to inflamed tissues, ultimately leading to the events resulting in parturition, such as increased prostaglandin synthesis, increased uterine contractile activity, and collagen degradation. PTD has been reported to be associated with increased production of proinflammatory cytokines including IL1β, IL6, TNFα and others [3,[7][8][9]. In this study, we confirmed increased expression of several of these proinflammatory cytokines along with increased expression of proinflammatory chemokines in mice undergoing LPS-induced PTD.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The cytokines, among other putative effects, recruit leukocytes to inflamed tissues, ultimately leading to the events resulting in parturition, such as increased prostaglandin synthesis, increased uterine contractile activity, and collagen degradation. PTD has been reported to be associated with increased production of proinflammatory cytokines including IL1β, IL6, TNFα and others [3,[7][8][9]. In this study, we confirmed increased expression of several of these proinflammatory cytokines along with increased expression of proinflammatory chemokines in mice undergoing LPS-induced PTD.…”
Section: Discussionsupporting
confidence: 81%
“…The innate immune response to LPS is mediated by the TLR4 membrane receptor, leading to increased production of the proinflammatory cytokines including IL1α, IL1β, IL6, TNFα, and IFNγ, in part through activation of the transcription factor NFκB [7,20]. These proteins enter a positive feedback loop with NFκB that amplifies the inflammatory response by increasing cytokine production which stimulates further activation of NFκB [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human placenta, IL8 production is increased after spontaneous labour and was localised in the perivascular area of foetal vessels in third-trimester placenta (Elliott et al 1998). The increase in IL8 mRNA levels corresponds to the influx of PMNs and other immune cells like macrophages that has been found immediately before parturition (Yellon et al 2003) and its known synergism with the effects of PGE 2 in attracting PMNs to skin sites (Foster et al 1989, Colditz 1990) suggests a possible role for IL8 in initiation and progression of labour through activation of PMNs, which release proteolytic enzymes, such as collagenases and elastases that degrade ECM contributing together with apoptosis to foetal membrane rupture (Osmers et al 1992, Winkler & Rath 1996, Moore et al 2006.…”
Section: Genes Related To Immune Responsementioning
confidence: 96%
“…Substance P and calcitonin gene related peptide concentrations increase in uterocervical afferents and substance P concentration increases in cervical stromal tissue just prior to the onset of labor, 25,26 suggesting that afferent released neuropeptides could play a role in cervical ripening by enhancing plasma extravasation leading to edema, increasing leukocyte migration, and enhancing cytokine production from leukocytes into the cervical tissue. 27 Indeed, transection of sensory nerves to the uterine cervix results in obstructed labor in rodents, 28 although it is unclear whether this is due to an effect on cervical ripening or on expulsive efforts in late labor. 8 Nonetheless, the potentially huge increase in neuropeptide release from uterocervical afferents in late pregnancy predicted by the current study ( fig.…”
Section: Discussionmentioning
confidence: 99%